Arginine metabolism in Rainbow Trout fingerlings requirements, biosynthesis and interactions with dietary electrolytes and basic amino acids - Chiu, Yvonne
Experiments were conducted to determine the effect of level of feeding (i.e. restricted feeding and feeding to satiation) and mixtures of Na, K and Cl (Na + K - C1 = -200, 0 and +200 meq/kg diet) on the arginine requirement of rainbow trout fingerlings. Based on growth and efficiency of feed conversion, arginine requirement was lower when fish were fed to satiation that when they were fed at a restricted level. The arginine requirement was increased when fish were fed diets containing 200 meq/kg as compared to -200 or 0 meq/kg [Na + K - Cl]. Fish receiving 0 meq/kg were more sensitive to dietary excesses and interactions among basic amino acids resulting in depressed growth, and were observed to contain markedly higher muscle free histidine concentrations and lower lysine concentrations than those receiving -200 meq/kg. Hepatic arginase activity, arginine and lysine catabolism in tissue slices and histidine-pyruvate aminotranserase were altered by dietary electrolytes. Crbamyl phosphate synthetase (CPS), ornithine transcarbamylase (OTC)and arginase activities were not affected by dietary protein level. Arginase activities were higher in the liver and lower in the kidney, while CPS and OTC activities were higher in the kidney and muscle and lower in the liver in starved than in fed fish. L-[1-14C] ornithine~HCl and L-[carbamyl-14C]citrulline injected intraperitoneally, were incorporated into tissue arginine. No detectable incorporation into arginine was observed with NaH14CO3. The detection of 28% of the 14C-label in the guanidino-14C position using 14C-citrulline and none using 14C-ornithine as the precursor is consistent with arginine biosynthesis via the urea cycle. Growth and efficiency of feed conversion were not affected when half of dietary arginine was replaced by an equimolar amount of citrulline but were slightly depressed with ornithine replacement. Glutamate was ineffective in replacing arginine. It appears that in trout, the ornithine and citrulline can be used as precursors of arginine, with different rates of conversion.